A dimensão cultural da educação em prisões - Silva, Mazukyevicz Ramon Santos do Nascimento (2016)
Taking criminology criticism as a theoretical framework, and materialist dialectics as a method employed in the investigations, the research in question investigates, in a broad perspective, what can education in contexts of deprivation of liberty, and a narrow perspective, the redefinition of possibilities of education in prisons practiced in the Brazilian scene today, to an education in prisons oriented transformation of culture around the criminal cases. With critical criminology it is possible to identify at least two dimensions, antagonistic, but complementary, from which the education of detention contexts is presented. The first of these dimensions, called moral dimension of education in prison, it appears as the dominant dimension in Western history in punitive rationality Brazilian law, in national education policy practiced prisons from Educating program for Freedom 2005, and national academic discourse. Its criminal paradigm backdrop of social defense and the legal discourse of crime, and understand crime as a phenomenon of individual and volitional causes, prison and useful measure, fair, equal and legitimate for the response to crime, education as an instrument for the rehabilitation of deprived of freedom, and society as a always available to acceptance of the morally transformed individual environment. On the other hand, the cultural dimension of education in prisons recognizes crime as a multifactorial phenomenon, the arrest as a political and economic response against the crime, education as a dialogical and plural process that must integrate the various actors who make up the prison universe and the role of the social group in the process of treatment of criminal matters. Concludes research that education in prisons can be re-signified, to abandon the idea of an education of the prisoner, and take the idea of education for a new culture, education for human rights, a culture of non-violence, implying then the need for greater opening of the prison to society, and society to prison, and the substitution of rehabilitation notion that underlies the education in prison in Brazil by the notion of reconciliation.